Eficácia de sulcadores de uma semeadora-adubadora e suas implicações na cultura da soja e nos atributos físicos de um Latossolo sob integração lavourapecuária - Andreolla, Veruschka Rocha Medeiros (2005)
The objective of this work was to verify the influence of pasture in side of agriculture-cattle integration on the physical characteristics of the ground, to evaluate the influence of these parameters and the staggered of a planter (connecting rod and record of cut) on the grain yield of the soy and to quantify the energy performance of the planter in ground submitted to the trampling of animals. An experiment in Oxissol, situated was become fulfilled in the Santa Maria Farm, Santa Tereza do Oeste - PR, in the period of April of 2003 the April of 2004. The delineation in subdivided parcels "Split Plot" entirely randomized was used. The main treatments had been composed by pasture with the ground humid or wet, pasture with alone dry and without pasture, with a capacity of 26 U.A. ha 1. The secondary treatments had been composites for the mechanisms staggered of the planter (double connecting rod or records for deposition of the seasoning). Each plot with a area 1600 m2 (50 x 32 m) and the subparcels had dimensions of 20 x 8 m, with area of 160 m2. Physical properties of the ground, parameters of performance of the tractor-planter set and grain yield of the soy had been evaluated. The values gotten in the experiments had shown the effect of the cattle trampling in compacting the ground in the layer until the 10 cm initial. The sharp peak in the resistance to the penetration the 5 cm can be indicating that the maximum mobilization of the resistance of the ground occurred at the depth 5 cm. The root of the soy had promoted the decompaction of the ground, showing a trend of return to the initial structural condition of it. The tension-deformation analysis corroborated the results of the assays of compacting in laboratory, as well as the deformation curve revealed consistent with the profiles of resistance to the penetration in the field. The action of the cattle trampling on the ground modified the density conditions and cone index, however was not enough to intervene with the demand of power in the three studied conditions. The planter with staggered of records had exerted minor power and snatch force and the speed of displacement of the set was about 6,4 % greater in relation to the staggered connecting rod. The grain yield of the soy was not modified significantly by the handling systems, but when the mechanism was used connecting rod in the planter, the production of grains bigger when was compared with the planter equipped with staggered of records.